Effect of N-acetyl-cysteine on the hypoxic ventilatory response and erythropoietin production: linkage between plasma thiol redox state and O2 chemosensitivity - Hildebrandt, Wulf; Bärtsch, Peter; Dröge, Wulf (Blood, 2002)
Oxygen-sensing chemoreceptors contribute significantly to the regulation of the respiratory drive and arterial PO2levels. The hypoxic ventilatory response (HVR)
Gesehen am 03.02.2021